2018
DOI: 10.1111/jgh.14360
|View full text |Cite
|
Sign up to set email alerts
|

Lean non‐alcoholic fatty liver disease patients had comparable total caloric, carbohydrate, protein, fat, iron, sleep duration and overtime work as obese non‐alcoholic fatty liver disease patients

Abstract: Non-alcoholic fatty liver disease patients had higher total caloric, calorigenic nutrients, grain, potato, fruit, iron, and overtime work but shorter sleep duration. Lean NAFLD patients had comparable total caloric, calorigenic nutrients, iron, sleep duration, and overtime work as obese NAFLD patients. These features could be used to the nutritional education and therapeutic guidance for lean NAFLD patients in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…It is worth mentioning that the prevalence of lean NAFLD showed a general upward trend in recent years, which has occurred in parallel with the increasing dietary fat and fructose consumptions both in Asia and in Western countries 11 . Similar to risk factors for overweight/obese NAFLD, lifestyle changes (e.g., decreased physical activity, sedentariness, high fat, and fructose intakes) may be also acquired risk factors for lean NAFLD 12 . Therefore, as the global burden of lean NAFLD increases, special attention should be paid to lean subjects with coexisting risk factors for the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the prevalence of lean NAFLD showed a general upward trend in recent years, which has occurred in parallel with the increasing dietary fat and fructose consumptions both in Asia and in Western countries 11 . Similar to risk factors for overweight/obese NAFLD, lifestyle changes (e.g., decreased physical activity, sedentariness, high fat, and fructose intakes) may be also acquired risk factors for lean NAFLD 12 . Therefore, as the global burden of lean NAFLD increases, special attention should be paid to lean subjects with coexisting risk factors for the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar to risk factors for overweight/obese NAFLD, lifestyle changes (e.g., decreased physical activity, sedentariness, high fat, and fructose intakes) may be also acquired risk factors for lean NAFLD. 12 Therefore, as the global burden of lean NAFLD increases, special attention should be paid to lean subjects with coexisting risk factors for the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, in a Chinese population, no substantial qualitative differences in diet were noted between those who were lean and had NAFLD versus obese individuals with NAFLD. 26 In general, even within the lean population, those with NAFLD tend to consume greater total calories. 27 Sedentary lifestyle is known to be associated with an increased prevalence of insulin resistance, however in lean individuals the role of a sedentary lifestyle has not yet been well established.…”
Section: Diet and Other Environmental Influencesmentioning
confidence: 99%
“…These studies indicate that NAFLD patients consume diets that are higher in sugars, carbohydrates, saturated fatty acids, and total fat, 60 while a higher consumption rate of processed food, animal protein (red meat), trans fat, saturated fats, and simple sugars aides the development of NAFLD 61 . A recent case–control study on 351 Chinese adults also confirmed these findings in lean NAFLD patients 62 . It is also proven that NAFLD patients tend to consume less insoluble dietary fibers than their healthy counterparts, while higher intake of dietary fibers from green vegetables, nuts, soy foods, and whole grain leads to lower NAFLD rates in populations 61,63 .…”
Section: Pathogenesismentioning
confidence: 73%